Assessment of Physico-chemical and Biological quality of Ground Water in the Residential Area of Bareilly City, UP, India - Zeba Jahan; Anamika Agrawal; Vivek (G-Journal of Environmental Science and Technology, 2018)
Supply of good quality drinking water is very important for the development and improvement of community. Health of any community is related to the safe drinking water. Most of the drinking water supply comes from the underground water in the city. In this study, analysis of physico-chemical and microbial quality was done in the five residential area of Bareilly city by using standard method. The physico-chemical characters of all the five drinking water samples were within the recommended permissible level of WHO. In all the five water samples the total plate count was above the WHO guideline values (<10CFU’s/ml). The result of microbial activity demonstrates that water is polluted with fecal coliform and need to disinfect before use and in physico- chemical investigation it was found that the maximum parameter were not at the level of pollution. So, ground water samples of all the area satisfied the requirement for the use in various purposes.